Alcohol use during pregnancy and associated factors among pregnant women in Sub-Saharan Africa: further analysis of the recent demographic and health survey data - Bezawit Mulat; Wallelign Alemnew; Kegnie Shitu (BMC, 2022)
Abstract Background Alcohol drinking during pregnancy is towering despite the well-established proof of its unfavorable pregnancy results and destitute child improvement. Despite such enormous consequences, there are limited data that explore the extent of alcohol drinking and its associated factors among mothers during pregnancy in sub-Saharan Africa. Objective This study aimed to assess the prevalence and associated factors of alcohol consumption during pregnancy among pregnant mothers in sub-Saharan Africa. Method A community-based crossectional demographic and health survey was conducted from 2013 to 2017 among four Sub-Sahara African countries: Burundi, Ethiopia, Liberia, and Zimbabwe. A two-stage stratified sampling technique was employed to select the participants. Multivariable Logistic regression analysis was used to identify factors associated with alcohol consumption during pregnancy. A p-value less than 0.05 and a 95% confidence interval were used to declare statistical significance. Result A total of 3953 weighted sample of pregnant mothers were included in the study. The mean age of the participants was 27.3 (± 6.8) years with an age range of 15-49 years. The overall prevalence of alcohol use during pregnancy was 22.8% with (95% CI (21.5, 24)) and it was significantly associated with increased age (AOR = 1.02, 95% CI (1.01, 1.04)), Muslim religion follower ( AOR = 0.07, 95% CI (0.05,0.11), husband/partner's educational status( primary (AOR = 0.7,95% CI (0.55,0.84), secondary (AOR = 0.53, 95% CI ( 0.41,0.7)) and higher (AOR = 0.49, 95% CI (0.31,0.8), being currently working (AOR = 1.5,95% CI ( 1.09,1.55), having ANC visit ( AOR = 0.82, 95% C I(0.68,0.98) and increased gravidity ( AOR = 0.93,95% CI( 0.86,0.99). Conclusion Alcohol drinking during pregnancy was high among pregnant women in sub-Saharan African countries. Maternal age, religion, husband educational status, current working status of the mother, presence of ANC visit, and gravidity of the mother were factors that have a significant association with alcohol drinking during pregnancy. This calls for a tailored behavior change intervention to reduce alcohol use during pregnancy. More emphasis should also be given to pregnant women with no ANC visit, lower gravidity, and an illiterate husband, currently working and Christianity followers.